Assessing Rural Municipality Standardization: A Policy Position Paper - Adhikari, Khagendra Prasad (NPRC Journal of Multidisciplinary Research, 2025)
The Policy position paper aims to assess the standard of rural municipality as the grass root foundation of communities This public policy position paper addresses the need to strengthen the service delivery of local government units in Nepal by developing the holistic structure as mention in the constitution of Nepal. It recognizes the significance of standard of mechanism of rural municipality for the smooth administration and development. The paper discusses the current challenges, including infrastructure deficits, digital divides, policy gaps, and presents the ways forward to overcome these hurdles and maximize the transformative potential of Rural Municipality.The policy position paper also highlights best practices from Finland. New Zealand, Sweden, Germany and United states in utilizing standard frame work for local government service delivery. The objective of this paper is to provide a comprehensive assessment of the current standard of rural municipality in the Nepalese local government units, propose actionable ways forward, and emphasize the significance of smooth administration for achieving sustainable development. Methodologically, the study uses qualitative thematic analysis of constitutional texts, policy documents, and interviews from policy dialogues. The findings suggest the need for clear legal mandates, capacity building, and bottom-up governance models. This paper concludes with specific policy recommendations and implementation strategies to support sustainable and inclusive rural development.